The Impact of Nationalism on Democracy: Historical, Theoretical and Intellectual Perspectives - Ali Çiçek (İmgelem)
This study explores in depth the complex relationship between nationalism and democracy, which have played a central role in shaping modern political systems. While nationalism seeks to create a collective sense of belonging based on a common identity, culture and history, democracy is defined as a system of government in which political authority derives from popular consent and promotes participation and equality. The study examines the historical development of nationalism and democracy, the theoretical links between these two concepts and the ideas presented by leading thinkers. While Mill emphasized the importance of national unity for the success of democratic governments, Rousseau and Renan discussed the role of national identity and common will in the functioning of democracy. Through the contributions of thinkers such as John Stuart Mill, Jean-Jacques Rousseau and Ernest Renan, the supporting and conflicting dynamics between nationalism and democracy are analyzed. This article argues that while nationalism can support democracy, it can also threaten democratic principles, especially when it is exclusionary and ethnically based. It also shows how populist nationalism undermines democracy and upsets the balance between these two concepts. By examining the historical and theoretical contexts of nationalism and democracy, the findings of the study help us understand the impact of these two concepts on modern political systems. At a time when globalization and regional integration are challenging the traditional boundaries of the nation-state, understanding this relationship is critical to assessing the impact of the dynamics between nationalism and democracy on political practices.